Pollen Tube Discharge Completes the Process of Synergid Degeneration That Is Initiated by Pollen Tube-Synergid Interaction in Arabidopsis . Issue 1 (30th July 2015) - Leydon, Alexander R.; Tsukamoto, Tatsuya; Dunatunga, Damayanthi; Qin, Yuan; Johnson, Mark A.; Palanivelu, Ravishankar
Abstract : Pollen tube arrival at a synergid cell promotes its degeneration, and cytoplasmic discharge from the tube completes the process. Abstract: In flowering plant reproduction, pollen tube reception is the signaling system that results in pollen tube discharge, synergid degeneration, and successful delivery of male gametes (two sperm cells) to the site where they can fuse with female gametes (egg cell and central cell). Some molecules required for this complex and essential signaling exchange have been identified; however, fundamental questions about the nature of the interactions between the pollen tube and the synergid cells remain to be clarified. Here, we monitor pollen tube arrival, pollen tube discharge, and synergid degeneration in Arabidopsis ( Arabidopsis thaliana ) wild type and in male and female gametophytic mutants that disrupt development and function of the gametophytes. By combining assays used previously to study these interactions and an assay that facilitates simultaneous analysis of pollen tube discharge and synergid degeneration, we find that synergid degeneration could be initiated without pollen tube discharge. Our data support the hypothesis that pollen tube-synergid contact, or signaling via secreted molecules, initiates receptive synergid degeneration. We also find that when pollen tubes successfully burst, they always discharge into a degenerated synergid. In addition to this pollen tube-dependent promotion of synergid degeneration, we also show that a basal developmental pathway mediates synergid degeneration in the absence of pollination. Our results are consistent with the model that a complex set of interactions between the pollen tube and synergid cells promote receptive synergid degeneration.